Grassland biodiversity and ecosystem functions benefit more from cattle than sheep in mixed grazing: A meta-analysis. (1st July 2023) - Su, Jishuai; Xu, Fengwei; Zhang, Yi
Abstract: Grasslands have been widely grazed for livestock production by cattle and sheep. However, previous studies have mainly focused on the impacts of single-species grazing on grassland biodiversity and ecosystem functions; the effects of mixed grazing of cattle and sheep remain largely unknown. We conducted a meta-analysis to examine the impacts of mixed grazing and analyzed the relative roles of cattle and sheep on grassland biodiversity and multiple ecosystem functions. Mixed grazing studies mainly originated from Europe, the USA, and China. Generally, cattle and sheep exhibited distinctive impacts on grassland biodiversity and functions in single-species and mixed grazing regimes. Cattle grazing alone increased plant diversity and soil organic carbon content (SOC), while sheep grazing alone had little impact. Compared to single-species grazing, mixed grazing generally increased plant density and richness of insect herbivores and decreased soil nematode richness, but did not alter plant biomass, soil nitrogen, or nematode abundance. Cattle in the mixed grazing regime increased plant diversity, biomasses of forbs and legumes, SOC, and liveweight gains of livestock. The mixed grazing impacts were further regulated by climate conditions, grazing intensity, and grazing duration. Our findings provide compelling evidence that mixed grazing benefits biodiversity, soil carbon sequestration, livestock production, and community structure of grasslands, and cattle are more influential than sheep in creating the benefits of mixed grazing for sustainable management of grasslands. Graphical abstract: Image 1 Highlights: Mixed grazing benefits grassland biodiversity and soil carbon sequestration. Cattle influence more than sheep in the effects of mixed grazing on grassland. Climate, grazing duration and intensity influence the impacts of mixed grazing.